Occupational hypersensitivity pneumonitis in a koji brewer. Issue 3 (19th January 2018) - Ishiguro, Takashi; Kawai, Shoko; Kojima, Ayako; Shimizu, Yoshihiko; Kamei, Katsuhiko; Takayanagi, Noboru
Key Clinical Message: Koji is a fermenting agent used in many traditional Japanese foods, and Aspergillus oryzae is the most frequently used microorganism in koji production. Few cases of hypersensitivity pneumonitis due to A. oryzae have been reported. However, physicians should recognize the disease because of the increasing globalization of food production. Abstract : Koji is a fermenting agent used in many traditional Japanese foods, and Aspergillus oryzae is the most frequently used microorganism in koji production. Few cases of hypersensitivity pneumonitis due to A. oryzae have been reported. However, physicians should recognize the disease because of the increasing globalization of food production.